Defining a mood stabiliser: novel framework for research and clinical practice. Issue 4 (20th July 2018) - Malhi, Gin S.; Porter, Richard; Irwin, Lauren; Hamilton, Amber; Morris, Grace; Bassett, Darryl; Baune, Bernhard T.; Boyce, Philip; Hopwood, Malcolm J.; Mulder, Roger; Parker, Gordon; Mannie, Zola; et al.
Summary: The term 'mood stabiliser' is ill-defined and lacks clinical utility. We propose a framework to evaluate medications and effectively communicate their mood stabilising properties – their acute and prophylactic efficacy across the domains of mania and depression. The standardised framework provides a common definition to facilitate research and clinical practice. Declaration of interest: The Treatment Algorithm Group (TAG) was supported logistically by Servier who provided financial assistance with travel and accommodation for those TAG members travelling interstate or overseas to attend the meeting in Sydney (held on 18 November 2017). None of the committee were paid to participate in this project and Servier have not had any input into the content, format or outputs from this project.